Watching Jude Law Digging a Hole: Negative Dialectics and the Audience in HBO/Punchdrunk’s The Third Day: Autumn - Kampmann Walther, Bo (Peripeti, 2025)
This article1 is based on Punchdrunk/Sky’s The Third Day: Autumn, which was experienced as a livestream featuring Jude Law in a 12-hour event on HBO’s Facebook page in 2020, during the Covid-19 lockdown. Through an analysis of audience responses in social media comments to Law as both a person and a character, I discuss shifts in realism within the reception, while examining the relationship between fiction and reality. This leads to an interpretation of the streaming event as a variation of immersive theatre, while acknowledging the differences in audience positioning due to the medium. Within this analytical framework and the examination of the dimension of reality, I draw comparisons to Theodor Adorno’s reading of Beckett’s Endgame; a discussion that extends to the type of critique that emerges in the comment section of the Autumn livestream. I hope to demonstrate that the way this televised live event, through Law’s performance, shifts the boundaries of representational fiction challenges Adorno’s idea of negative dialectics and the transparency between thought and object. What this means is that the social media comments can be viewed as a form of ‘critique’ that may be even more critical than the explicitly proclaimed criticism, even if it originates from amateurs rather than trained professionals and reviewers. It becomes a critique that is more closely aligned with what one journalist reviewing The Third Day: Autumn referred to as “just reality”, rather than fiction striving conceptually to imitate reality.